Adaptive diversity of incisor enamel microstructure in South American burrowing rodents (family Ctenomyidae, Caviomorpha) - Vieytes, Emma Carolina (2007)
The aim of this study was to analyse the morphofunctional and adaptive significance of variation in the upper incisor enamel microstructure of South American burrowing ctenomyids and other octodontoid taxa. We studied the specialized subterranean tooth-digger †Eucelophorus chapalmalensis (Pliocene - Middle Pleistocene), and compared it with other fossil and living ctenomyids with disparate digging adaptations, two fossorial octodontids and one arboreal echimyid. Morphofunctionally significant enamel traits were quite similar among the species studied despite their marked differences in habits, digging behaviour and substrates occupied, suggesting a possible phylogenetic constraint for the Octodontoidea. In this context of relative similarity, the inclination of Hunter-Schreger bands, relative thickness of external index (EI) and prismless enamel zone were highest in †Eucelophorus, in agreement with its outstanding craniomandibular tooth-digging specialization. Higher inclination of Hunter-Schreger bands reinforces enamel to withstand high tension forces, while high external index provides greater resistance to wear. Results suggest increased frequency of incisor use for digging in †Eucelophorus, which could be related to a more extreme tooth-digging strategy and/or occupancy of hard soils. Higher external index values as recurring patterns in distant clades of tooth-digging rodents support an adaptive significance of this enamel trait.